COVID-19 Epidemic in Argentina: Worsening of Behavioral Symptoms in Elderly Subjects With Dementia Living in the Community - Cohen, Gabriela; Russo, María Julieta; Campos, Jorge A.; Allegri, Ricardo F. (Frontiers in Psychiatry, 2020)
Our objective was to study to what extend COVID-19 quarantine had affected behavioral symptoms in subjects with dementia after the first 8 weeks of quarantine. Family members were invited to participate in a questionnaire survey. The sample consisted of family caregivers (n=119) of persons with AD or related dementia living at home. We designed a visual analog scale to test the level of the burden of care of family members. Items inquired in the survey included type and setting (home or day care center) of rehabilitation services (physical /occupational/cognitive rehabilitation), change in psychotropic medication and in behavioral symptoms that subjects with dementia experienced before and during the epidemic. Characteristics of people with dementia and their caregivers were analyzed with descriptive statistics, using the chi-square tests, p <0.01 was considered significant. Results: The sample included older adults with dementia. Mean age: 81,16 ( 7.03), 35 % of the subjects had more than 85 years of age. Diagnosis were: 67 % Alzheimer's Dementia, 26 % mixed Alzheimer's Disease. Stages were: 34.5 % mild cases, 32 % intermediate stage, 33 % severe cases as per Clinical dementia Rating score. In 67 % of the sample a family member was the main caregiver. Important findings were increased anxiety (43 % ); insomnia (28% ); depression (29 %); use of psychotropics and worsening gait disturbances (41 %). Anxiety, depression and insomnia were more prevalent in subjects with mild dementia, compared to subjects with severe dementia. We analyzed the type and pattern of use of rehabilitation services before and during the isolation period and we observed that as a rule, rehabilitation services had been discontinued in most subjects due to the quarantine. We concluded from our analysis that during COVID 19 epidemic there was a deterioration of behavioral symptoms in our population of elderly dementia subjects living in the community. Perhaps our findings are related to a combination of social isolation, lack of outpatient rehabilitation services and increased stress of family caregivers. It is necessary to develop a plan of action to help dementia subjects deal with the increased stress that this epidemic imposed on them.